2015
DOI: 10.1016/j.jpor.2015.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Loss of occlusal support affects the decline in activities of daily living in elderly people receiving home care

Abstract: Our results suggest that the loss of occlusal support may be an important factor in the decline of ADL in elderly people receiving home care, especially slightly dependent people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 18 publications
0
27
0
Order By: Relevance
“…Currently, the number of older people is increasing worldwide, and this tendency is especially prominent in Japan, which has the highest rate of population ageing in the world . With the increase in the older population, medical care costs will increase accordingly, and the need for preventative nursing care is becoming a critical Japanese social problem .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the number of older people is increasing worldwide, and this tendency is especially prominent in Japan, which has the highest rate of population ageing in the world . With the increase in the older population, medical care costs will increase accordingly, and the need for preventative nursing care is becoming a critical Japanese social problem .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the present findings are generally consistent with those of previous reports showing that the loss of posterior teeth occlusion might cause functional decline among older people. It has been reported that the loss of posterior occlusal support was significantly correlated with decremental changes in the BI . However, these previous reports roughly classified posterior teeth occlusion according to the presence or absence of at least one occlusal support among posterior teeth.…”
Section: Discussionmentioning
confidence: 94%
“…The influence of occlusal support on physical function has been demonstrated. Loss of occlusal support was associated with poorer mobility, increased risk of incident falls and decline in walking speed because loss of occlusal support affects body balance control . Moreover, a community‐based cohort study demonstrated that association between impaired dental occlusion and sarcopenia .…”
Section: Discussionmentioning
confidence: 99%